Cervical cancer screening coverage in urban and rural areas: its determinants - Juminten Saimin; Satrio Wicaksono; . Ashaeryanto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Cervical cancer is a woman’s health problem that is still widespread throughtout the world, especially in developing country such as Indonesia. The high incidence of cervical cancer related with early detection program. Visual inspection of acetic acid (VIA) is used as an alternative screening method because it is easier, cheaper and effectiveness is not much different from the Pap test. The most participant in urban and rural areas was the age group 31-40 years old, low parity, and first intercourse at ≥ 17 years old. There was asscociation between cervical cancer screening coverage with education level, knowledge and distance of service facilities. There were significant difference of education level (p = 0.000), knowledge (p = 0.000) and distance of service facilities of urban and rural participant (p = 0.000). There was no significant differences in family support of urban and rural participant (p = 0.224).